Virtual Inertial Control Strategy Based on Fuzzy Logic Algorithm for PMSG Wind Turbines to Enhance Frequency Stability - Li, Qun; Ren, Bixing; Li, Qiang; Wang, Dajiang; Tang, Weijia; Meng, Jianhui; Wu, Xiaolong (Frontiers in Energy Research, 2022)
With the increase of the penetration rate of wind power in the power grid, the high proportion of renewable energy and the high proportion of power electronic equipment in the power system will continuously reduce the inertia of the grid, and the frequency stability of the system will be seriously affected. The inertia of the system is an important parameter for system frequency regulation and stability calculation. For this reason, a virtual inertial control technology based on fuzzy logic control is proposed in this paper, which is used for wind turbines to participate in grid frequency regulation. In this method, based on power tracking, a fuzzy logic controller is designed to adjust the frequency adjustment coefficient adaptively, and fuzzy logic rules are used to optimize the power tracking curve online. Finally, by building a hardware-in-the-loop real-time simulation platform, the effectiveness of this method in providing system frequency support and improving the frequency response of the power grid is verified.